A Workshop to Help Students Integrate Sources into Their Writing - Vode, Dzifa; Raisig, Shawn (Journal of Academic Writing, 2016)
Inexperienced academic writers often have difficulty understanding and implementing academic intertextual practices, i.e. interpreting, extrapolating and integrating primary and secondary sources into their own texts. To address this need, we developed a workshop with learning stations. We identified five key difficulties students face and created seven exercises that address them. In the workshop, participants move from station to station, working on the exercises at their own pace by using pre-prepared materials at the stations. In this paper, we describe how we devised the workshop based on analysis of both the problem and the contexts in which the workshop has been carried out. Detailed descriptions for each exercise as well as a dramaturgy of the workshop are included; sample texts and handouts for each station can be found in the Appendix. Based on anecdotal participant feedback, we discuss advantages and disadvantages of the different exercises and of the workshop set-up. With the information provided, readers should be able to replicate this workshop and adapt the exercises to their own educational settings.